2006: World development indicators (The World Bank, 2006)
Looking for accurate, up-to-date data on development issues? World Development Indicators, the World Bank's respected statistical publication presents the most current and accurate information on global development on both a national level and aggregated globally. The Print edition allows you to consult over 800 indicators for some 150 economies and 14 country groups in more than 80 tables. It provides a current overview of the most recent data available as well as important regional data and income group analysis in six thematic chapters: World View, People, Environment, Economy, States and Markets, and Global Links. The CD-ROM* editions contain 44 years of time series data for more than 200 countries from 1960-2004, single-year observations, and spreadsheets on many topics. It contains more than 1,000 country tables and the text from the World Development Indicators 2006 print edition. The Windows? based format permits users to search for and retrieve data in spreadsheet form, create maps and charts, and fully download them into other popular software programs for study or presentation purposes. * The CD-ROM system requires Windows 98 or NT 4.0 or later, 20 MB of available hard disk space, 32 MB of RAM, and 2 MB of video memory. 64 K color video display recommended. Microsoft Internet Explorer version 4.0 or higher and sound card optional.